Level of Accessibility, Connectivity of Existing Road Networks in Supporting Mobility of Productive Area (Case Study: Sidenreng Rappang District) - , Muhammad Taufik; Hakzah; Misbahuddin (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Sidenreng Rappang Regency, South Sulawesi Province, Indonesia, is one of the regions with significant potential in the agricultural sector. Improving the economy through the agricultural sector needs to be balanced with the role of infrastructure, especially road networks. The purpose of this research is to determine the potential of the area based on the accessibility, connectivity and mobility of the road network with a focus on the distribution of agricultural products. The descriptive quantitative research method uses SWOT analysis with data collection from 30 respondents from the stakeholder side using a questionnaire survey. The research results based on the regional potential analysis show that rice, coconut and laying hens are the leading commodities. The analysis of the road network for the accessibility aspect shows that five out of eleven sub-districts still have poor accessibility, the connectivity aspect shows that each area is already connected, and the mobility aspect shows that the mobility index has not yet been achieved in three out of eleven sub-districts. The results of the SWOT analysis of the strategy for improving the road network based on the strengths and opportunities (SO) are as follows: improving the road network according to its roles and functions, maximising technical programmes according to the role of the regional budget (APBD), and making investments in infrastructure strengthening adapted to the region's potential.